An O‐Glycosylation of Fibronectin Mediates Hepatic Osteodystrophy Through α4β1 Integrin. (3rd August 2016) - Sens, Carla; Altrock, Eva; Rau, Katrin; Klemis, Verena; von Au, Anja; Pettera, Stefan; Uebel, Stephan; Damm, Timo; Tiwari, Sanjay; Moser, Markus; Nakchbandi, Inaam A
ABSTRACT: Patients with cholestatic liver disease experience increased fracture risk. Higher circulating levels of a fibronectin isoform called oncofetal fibronectin (oFN) were detected in a subset of such patients. Administering this isoform to mice suppresses osteoblast differentiation and diminishes bone mineral density in vivo, suggesting it is responsible for bone loss in cholestatic liver disease. The aim of this study was to define the mechanism by which oFN affects osteoblast function and evaluate possible modifiers in experimental hepatic osteodystrophy. The fibronectin isoform oFN is characterized by the presence of various glycosylations. In line with this, adding oFN that underwent enzymatic O‐deglycosylation to osteoblasts normalized nodule formation in vitro. Of three possible O‐glycosylation sites in oFN, only a mutation at AA 33 of the variable region or binding of this glycosylated site with an antibody normalized osteoblast differentiation. Because the responsible site is located in the variable region of fibronectin, which binds to α4β1 or α4β7 integrins, these integrins were evaluated. We show that integrin α4β1 mediates the inhibitory effect of oFN both in vitro as well as in vivo. In a hepatic osteodystrophy mouse model, we demonstrate that liver fibrosis is associated with increased circulating oFN and diminished BMD. In addition, trabecular bone loss induced by oFN injection or fibrosis induction could be prevented by either administering an antibody that binds to α4 integrin (PS/2) or the CS1 peptide, which contains a binding site for α4β1 integrin. In summary, oFN inhibits osteoblast activity. This is because of an O‐glycosylation in the variable region that results in decreased integrin‐mediated signaling. This deleterious effect can be thwarted by binding α4β1 integrin. Thus, we have characterized the defect and the receptor mediating bone loss in patients with hepatic osteodystrophy and evaluated possible therapeutic interventions in a murine model. © 2016 American Society for Bone and Mineral Research.